2019
DOI: 10.1002/mp.13385
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter CT phantoms public dataset for radiomics reproducibility tests

Abstract: PurposeThe aim of this paper is to describe a public, open‐access, computed tomography (CT) phantom image set acquired at three centers and collected especially for radiomics reproducibility research. The dataset is useful to test radiomic features reproducibility with respect to various parameters, such as acquisition settings, scanners, and reconstruction algorithms.Acquisition and validation methodsThree phantoms were scanned in three independent institutions. Images of the following phantoms were acquired:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…One of the most serious problems is the reliability of the abundant imaging-derived signatures proposed by radiomics [42]. Reproducibility of radiomics has been demonstrated to be vital for its use in clinical practice and many studies have put effort into testing the reproducibility of radiomics results [43][44][45]. However, in this study, we found that there is currently a lack of authentication on the reliability of radiomics signatures in radiomics research (single-center studies accounted for the majority of studies).…”
Section: Discussionmentioning
confidence: 79%
“…One of the most serious problems is the reliability of the abundant imaging-derived signatures proposed by radiomics [42]. Reproducibility of radiomics has been demonstrated to be vital for its use in clinical practice and many studies have put effort into testing the reproducibility of radiomics results [43][44][45]. However, in this study, we found that there is currently a lack of authentication on the reliability of radiomics signatures in radiomics research (single-center studies accounted for the majority of studies).…”
Section: Discussionmentioning
confidence: 79%
“…Researchers should thus be encouraged to feed the existing databases (The Cancer Imaging Archive-TCIA, The Cancer Genome Atlas-TCGA, response to drug or radiation therapy -RIDER). Publicly available phantom datasets, intended for radiomics reproducibility tests, could help assess the influence of acquisition settings in order to eliminate non-robust radiomic features [ 113 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Publicly available datasets like the RIDER dataset 10 help to gain knowledge about the impact of varying factors in radiomics [ 121 ]. Also, the availability of a public phantom dataset, intended for radiomics reproducibility tests on CT, could help to further assess the influence of acquisition settings in order to eliminate non-robust radiomic features [ 128 ]. However, studies are needed to show if robustness data acquired on a phantom can be translated to the human.…”
Section: Current Limitations In Radiomicsmentioning
confidence: 99%